Echinodermata community structure and ecological implications at Gili Island, Gresik Regency, East Java, Indonesia - Irawanti, Elvina; Yogama, Clint Devan (Journal of Marine Resources and Coastal Management, 2024)
This study investigates the abundance, diversity, and distribution of Echinodermata species across three different stations at Gili Island, Gresik Regency, East Java. A total of five species were identified, with four species from the class Asteroidea (Linckia laevigata, Culcita novaeguineae, Protoreaster nodosus, and Acanthaster planci) and one from the class Ophiuroidea (Ophiocoma scolopendrina). The study employed the Belt Transect Method for sampling, and the results revealed varying levels of abundance and diversity among the stations. Station 2, dominated by coral reefs, exhibited the highest abundance (0.16 ind/m²), followed by Station 1 (0.14 ind/m²) with seagrass and macroalgae ecosystems, and Station 3 (0.13 ind/m²) with a mix of coral reefs and macroalgae. The diversity index (H') indicated moderate diversity across all stations, with Station 3 having the highest index value. Additionally, the uniformity index showed high species evenness, particularly at Station 3, and the dominance index was low, suggesting no single species dominated the communities. The study highlights the significant influence of habitat complexity, particularly coral reefs and seagrass beds, on Echinodermata populations. The results underscore the importance of these ecosystems in supporting biodiversity and maintaining ecological balance in marine environments.